2016
DOI: 10.5812/cardiovascmed.28952
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 serum levels are independently associated with microalbuminuria in chronic heart failure outpatients

Abstract: Background:Galectin-3 (Gal-3) is a novel biomarker reflecting inflammation status and fibrosis involving worsening of both cardiac and renal functions.Objectives:The aim of this study was to evaluate the relationship between Gal-3 serum levels and microalbuminuria in a group of chronic heart failure (CHF) outpatients.Patients and Methods:We enrolled CHF outpatients having stable clinical conditions and receiving conventional therapy. All patients underwent clinical evaluation, routine chemistry analysis, echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Incident albuminuria was examined only in the Framingham Offspring Study and no relationship with galectin-3 was found [17]. An independent association between galectin-3 concentration and microalbuminuria has been reported in individuals with chronic heart failure [25].…”
Section: Discussionmentioning
confidence: 99%
“…Incident albuminuria was examined only in the Framingham Offspring Study and no relationship with galectin-3 was found [17]. An independent association between galectin-3 concentration and microalbuminuria has been reported in individuals with chronic heart failure [25].…”
Section: Discussionmentioning
confidence: 99%
“…In outpatients with HF, increased serum levels of galectin-3 reflected increased neurohumoral activity and reduced eGFR, however, not myocardial function ( 42 ). In another study enrolling a group of outpatients with chronic HF, galectin-3 serum levels were significantly and independently associated with micro-albuminuria ( 43 ). However, Zhang et al ( 44 ) reported that for inpatients with HF, galectin-3 only predicted mortality associated with renal function for patients with an eGFR >60 ml/min/1.73 m 2 .…”
Section: Galectin-3 and Cardiovascular Diseasementioning
confidence: 99%
“…Both these novel biomarkers reflect different pathophysiological pathways compared with natriuretic peptides, i.e., cardiac remodeling related to fibrosis. Moreover, Gal-3 also seems associated to renal dysfunction [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%